The design and development of a study protocol to investigate Onchocerca volvulus, Loa loa and Mansonella perstans-mediated modulation of the metabolic and immunological profile in lean and obese individuals in Cameroon. - Benjamin Lenz; Beng Amuam Andrew; Manuel Ritter; Indulekha Karunakaran; Narcisse Victor Tchamatchoua Gandjui; Lucy Cho Nchang; Jayagopi Surendar; Anita Obi Bate Ebob; Alexandra Ehrens; Ute Klarmann-Schulz; Arcangelo Ricchiuto; Janina M Kuehlwein; et al. (PLoS ONE, 2023)
Background Life-style metabolic diseases are steadily rising, not only in developed countries, but also in low- and middle-income countries, presenting a global health problem. Metabolic disorders like type 2 diabetes and cardiovascular diseases are among the ten leading causes of death defined by the WHO in 2019. Results from animal and observational human studies suggest a connection between the decline in human helminth infections and rise of life-style-associated metabolic diseases in developing regions. This trial was designed to investigate filarial infections and their impact on metabolic diseases in Cameroon. We hypothesize that the induction of regulatory immune responses during filarial infection reduces obesity-induced low-grade inflammatory immune responses and thereby improves metabolic parameters, whereas anthelmintic treatment abolishes this protective effect. Methods/design Participants infected with Mansonella perstans, Onchocerca volvulus and/or Loa loa being lean (BMI <25), overweight (BMI >25 and <30) or clinically obese (BMI ≥30) from Littoral regions of Cameroon will be evaluated for their parasitological, immunological, metabolic and biochemical profile before and after treatment of their parasitic infections. Anthropomorphic measurements and a detailed questionnaire will complement our analysis. The investigation will assess blood immune cell populations, serum adipokines and cytokines that could be influenced by the parasite infection and/or metabolic diseases. Further, parameters like blood glucose, homeostatic model assessment of insulin resistance (HOMA-IR), circulating lipids and circulating makers of liver function will be monitored. Parameters will be assessed before treatment, 12 and 18 months after treatment. Conclusion The focus of this study is to obtain a comprehensive metabolic profile of the participants in rural areas of Cameroon and to investigate the relationship between filarial immunomodulation and metabolic diseases. This study will elucidate the effect of anti-filarial treatment on the metabolic and immunological parameters that partake in the development of insulin resistance, narrowing in on a potential protective effect of filarial infections on metabolic diseases. Trial registration doi.org/10.1186/ISRCTN43845142, ISRCTN43845142 February 2020 Trial title Effects of filarial parasite infection on type 2 diabetes Issue date: 27.10.22, V.1.